Coupling effects of laser assistance and tool rake angle on brittle-ductile transition in monocrystalline silicon - Guohui Li; Gangjie Luo; Jiafu Zhou; Yang Ou; Cheng Huang; Chaoliang Guan; Yifan Dai; Xiaoqiang Peng; Yupeng Xiong (Journal of Materials Research and Technology)
Laser-assisted turning (LAT) is an energy-field-assisted turning method developed to improve the machinability of hard and brittle materials, such as monocrystalline silicon. The thermal effect of the laser improving turning quality and extending tool life. However, the coupling influence mechanism between laser power and tool rake angle to the brittle–brittle transition (DBT) of monocrystalline silicon remains unclear. In this study, scratch experiments and molecular dynamics(MD) simulations were performed to explore this coupling influence mechanism. The research indicates that as temperature increases, the fracture toughness improvement(80 °C) and deformation mechanism transition(400 °C) of monocrystalline silicon are two critical nodes. Different tool rake angles respond differently to changes in material properties. At room temperature, negative rake angle tools exhibit a clear advantage. However, at high temperatures, a 0° rake angle tool can achieve a DBT depth of up to 829 nm. The tool rake angle and laser power need to be properly matched to provide the optimal DBT depth. In addition, a DBT depth model related to temperature and rake angle was established to accurately describe and predict the experimental results. These findings provide valuable insights for the selection of LAT process parameters to improve the processing quality of monocrystalline silicon.